Foot‐and‐mouth disease outbreaks due to an exotic virus serotype A lineage (A/AFRICA/G‐IV) in Algeria in 2017. Issue 1 (5th October 2018) - Pezzoni, Giulia; Bregoli, Arianna; Grazioli, Santina; Barbieri, Ilaria; Madani, Hafsa; Omani, Amel; Sadaoui, Hassiba; Bouayed, Nadera; Wadsworth, Jemma; Bachanek‐Bankowska, Kasia; Knowles, Nick J.; King, Donald P.; et al.
Abstract: This study describes the genetic characterization of serotype A viruses collected during outbreaks of foot‐and‐mouth disease (FMD) that occurred in Algeria in 2017. These are the first reports of clinical cases due to this serotype in the country since 1977. One complete genomic sequence (comprising 8, 119 nucleotides) and three additional near‐complete genomic sequences were generated. Phylogenetic analyses demonstrated that these viruses were classified within the A/AFRICA/G‐IV lineage, most closely related to viruses circulating in Nigeria between 2009 and 2015. These unexpected results motivate further studies to define the precise pathways by which this viral lineage has been introduced into North Africa in order to understand risks of future disease incursions into the region.